2019
DOI: 10.1158/0008-5472.can-19-1302
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 Inhibition Synergizes with Anti-PD-L1 Therapy in ARID1A-Inactivated Ovarian Cancer

Abstract: ARID1A, encoding a subunit of the SWI/SNF complex, is the most frequently mutated epigenetic regulator in human cancers and is mutated in over 50% of ovarian clear cell carcinoma (OCCC), a disease that currently has no effective therapy. Inhibition of histone deacetylase 6 (HDAC6) suppresses the growth of ARID1A-mutated tumors and modulates tumor immune microenvironment. Here we show that inhibition of HDAC6 synergizes with anti-PD-L1 immunecheckpoint blockade in ARID1A-inactivated ovarian cancer. ARID1A direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…123 This is consistent with the demonstration that HDAC6 inhibition can synergize with anti-PD-L1 therapy in a mouse model, raising the possibility that this combination may represent a novel therapeutic strategy. 124 In early work, prolyl hydroxylase domain-containing protein 2 (PHD2), encoded by EGLN1, has been identified as a potential hypoxia-inducible factor 1α (HIF1A)-dependent therapeutic target in clear cell carcinoma; 125 and screening of ARID1A-deficient cells has suggested that gemcitabine may be an effective therapeutic option in ARID1A-deficient tumors. 126 Post-Treatment Surveillance Current NCCN guidelines do not recommend clear cell carcinomaspecific post-treatment surveillance; 87 patients are followed up in the same way as patients with other histological tumor types.…”
Section: Radiotherapymentioning
confidence: 99%
“…123 This is consistent with the demonstration that HDAC6 inhibition can synergize with anti-PD-L1 therapy in a mouse model, raising the possibility that this combination may represent a novel therapeutic strategy. 124 In early work, prolyl hydroxylase domain-containing protein 2 (PHD2), encoded by EGLN1, has been identified as a potential hypoxia-inducible factor 1α (HIF1A)-dependent therapeutic target in clear cell carcinoma; 125 and screening of ARID1A-deficient cells has suggested that gemcitabine may be an effective therapeutic option in ARID1A-deficient tumors. 126 Post-Treatment Surveillance Current NCCN guidelines do not recommend clear cell carcinomaspecific post-treatment surveillance; 87 patients are followed up in the same way as patients with other histological tumor types.…”
Section: Radiotherapymentioning
confidence: 99%
“…Fukumoto et al showed that inhibition of HDAC6 synergizes with PD-L1 inhibitors in ARID1A-inactivated OC. These findings suggest a rationale for combining epigenetic modulators and PD-L1 inhibitors against OC [64].…”
Section: Monotherapy or Combination Therapy With Pd-l1 Inhibitors Inmentioning
confidence: 83%
“…Inhibition of HDACs lead to increased histone acetylation, resulting in increased gene expression [75]. Recently, both the HDAC inhibitor mocetinostat and inhibition of HDAC6 independently demonstrated a synergistic effect in combination with ICI, resulting in increased anti-tumor activity in NSCLC and ovarian cancer cell lines by increasing tumor antigen presentation and decreasing immune suppressive cell types [76,77]. Furthermore, in a phase I study, an adenovirus vector encoding the IL-12 gene was injected during surgery in the resection cavity walls of patients with recurrent high-grade glioma, followed by post-operative treatment with the oral activator for human IL-12, veledimex.…”
Section: Discussionmentioning
confidence: 99%